(untitled) (Research, Society and Development, 2022)
Historically, G6PD deficiency was reported for the first time in individuals who received doses of primaquine, the primary drug to be addressed in the study, to treat malaria, and triggered a symptomatic response with jaundice and a hematological field of erythroenzymopathies. In this sense, through an integrative review, the present research aimed to discuss the importance of pharmaceutical care and its relationship with the treatment of patients with G6DP enzyme deficiency. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common enzyme deficiency prevalent in many malaria-endemic countries. In this sense, patients with G6PD deficiency are susceptible to hemolysis during oxidative stress, which can occur from exposure to certain drugs, including 8-aminoquinolines used to treat Plasmodium vivax malaria. In this way, pharmaceutical care would become a tool for monitoring patients and managing problems that may occur during pharmacotherapy. Guiding, educating and implementing quantitative mechanisms for diagnosing and providing adequate radical cure in heterozygous women, who remain at risk of hemolysis.